2008
DOI: 10.1016/j.jvs.2008.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser ablation: Does standard above-knee great saphenous vein ablation provide optimum results in patients with both above- and below-knee reflux? A randomized controlled trial

Abstract: Background: Following above-knee (AK) great saphenous vein (GSV) endovenous laser ablation (EVLA) 40% to 50% patients have residual varicosities. This randomized controlled trial (RCT) assesses whether more extensive GSV ablation enhances their resolution and influences symptom improvement. Method: Sixty-eight limbs (65 patients) with varicosities and above and below-knee GSV reflux were randomized to Group A: AK-EVLA (n ‫؍‬ 23); Group B: EVLA mid-calf to groin (n ‫؍‬ 23); and Group C: AK-EVLA, concomitant bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 14 publications
2
64
1
Order By: Relevance
“…In fact, only that of Michaels et al 2 falls within the IQR of the national reference costs (£765-1355). 52 The study characteristics shown in Table 25 do not explain these variations. All the studies compared different treatments with stripping, so their costs relative to stripping can be calculated.…”
Section: Costsmentioning
confidence: 92%
See 3 more Smart Citations
“…In fact, only that of Michaels et al 2 falls within the IQR of the national reference costs (£765-1355). 52 The study characteristics shown in Table 25 do not explain these variations. All the studies compared different treatments with stripping, so their costs relative to stripping can be calculated.…”
Section: Costsmentioning
confidence: 92%
“…Of the total 36,000 varicose vein procedures captured in the 2009/10 national reference costs, almost 80% were conducted as day cases, the majority of which were a primary unilateral procedure without complications (84%). 52 The average cost of such procedures, inflated to 2011/12 with an inflation factor of 1.064, 144 is £1155 (IQR £765-1355). 52 The Table 25 includes one further UK cost study which was identified in a later search (see below).…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Incidence of hypoaesthesia, swelling, bruising and discomfort following EVLA are not rare, but these impairments are usually self-limited and often improve within months. 10,20 Hyperpigmentation along the course of the treated vein can also be seen at times, especially if the vein is above the fascial level and in thin individuals, but this complication also gradually fades over time. 10 The mean body mass index for our patients with hyperpigmentation following EVLA was significantly low and they were thin individuals.…”
Section: Discussionmentioning
confidence: 99%